Benefits of the Use of Mobile Applications for Learning a Foreign Language by Elderly Population - Klimova, Blanka (Procedia computer science, 2020)
At present, there is a rapid increase in the number of older population. These demographic changes obviously bring about a number of economic and social issues, which are, for instance, reflected in a rising number of aging diseases, such as dementia, characterized by cognitive impairment. Since there is no effective pharmacological treatment, country's governments are looking for policies and strategies, which would delay the aging process, and thus prolong an active life of aging population. One of these policies appears to be the use of technologies, respectively mobile applications, by elderly people. The purpose of this article is to discuss the use of mobile applications in learning foreign languages, such as English, by elderly people, as well as their benefits. Overall, mobile apps for learning a foreign language appear to be one of the tools which can promote well-being of older people. The results reveal there are many benefits of learning a foreign language by seniors. These include, for example, improvement of their cognitive performance, positive impact on their psyche, reduction of anxiety, gaining self-confidence, development of new social ties and feeling of self-realization, as well as learning of a new foreign language. However, research in this area is very scare, which is due to the lack of such apps for the elderly and consequently, due to the lack of the experimental studies in this field.
Keywords: older people; benefits; smartphones; EFL; mobile applications